FNA, core biopsy, or both for the diagnosis of lung carcinoma: Obtaining sufficient tissue for a specific diagnosis and molecular testing. Issue 5 (24th February 2015) - Coley, Shana M.; Crapanzano, John P.; Saqi, Anjali
Abstract : BACKGROUND: Increasingly, minimally invasive procedures are performed to assess lung lesions and stage lung carcinomas. In cases of advanced‐stage lung cancer, the biopsy may provide the only diagnostic tissue. The aim of this study was to determine which method—fine‐needle aspiration (FNA), core biopsy (CBx), or both (B)—is optimal for providing sufficient tissue for rendering a specific diagnosis and pursuing molecular studies for guiding tumor‐specific treatment. METHODS: A search was performed for computed tomography–guided lung FNA, CBx, or B cases with rapid onsite evaluation. Carcinomas were assessed for the adequacy to render a specific diagnosis; this was defined as enough refinement to subtype a primary carcinoma or to assess a metastatic origin morphologically and/or immunohistochemically. In cases of primary lung adenocarcinoma, the capability of each modality to yield sufficient tissue for molecular studies (epidermal growth factor receptor, KRAS, or anaplastic lymphoma kinase) was also assessed. RESULTS: There were 210 cases, and 134 represented neoplasms, including 115 carcinomas. For carcinomas, a specific diagnosis was reached in 89% of FNA cases (33 of 37), 98% of CBx cases (43 of 44), and 100% of B cases (34 of 34). For primary lung adenocarcinomas, adequate tissue remained to perform molecular studies in 94% of FNA cases (16 of 17), 100% of CBx cases (19 of 19), and 86% of B cases (19 of 22). No statistical difference was found among the modalities for either reaching a specific diagnosis ( p  = .07, Fisher exact test) or providing sufficient tissue for molecular studies ( p  = .30, Fisher exact test). CONCLUSIONS: The results suggest that FNA, CBx, and B are comparable for arriving at a specific diagnosis and having sufficient tissue for molecular studies: they specifically attained the diagnostic and prognostic goals of minimally invasive procedures for lung carcinoma. Cancer (Cancer Cytopathol) 2015;123:318–26. © 2015 American Cancer Society. Abstract : Lung lesions are frequently sampled under computed tomography guidance. Fine‐needle aspiration, core biopsy, and both are equivalent at providing tissue for histological, immunohistochemical, and molecular diagnoses.